ESTIMATION OF THERMAL IMAGER MINIMUM RESOLVABLE TEMPERATURE DIFFERENCE - Ahmed M.L. Al-Mzirawi; V. G. Kolobrodov; V. I. Mykytenko (Приборы и методы измерений)
The paper is devoted to improving the accuracy of determining the minimum resolvable temperature difference (MRTD) of thermal imagers by means of more sophisticated models of thermal images visual perception. An MRTD calculating algorithm, which is based on a more reliable approximation of the visual system modulation transfer function by Schultz, is considered. New expression for the bandwidth of Schultz's approximation, which does not depend on the angular size of the Foucault pattern bar, was obtained.